Realce tardio miocárdico por ressonância magnética cardíaca identifica risco para taquicardia ventricular na cardiopatia chagásica crônica - Mello, Ronaldo Peixoto de [UNIFESP] (2016)
Background: Invasive and non-invasive tests have been used to identify the risk of ventricular tachycardia in patients with Chagas' Cardiomyopathy. Cardiac Magnetic Resonance Imaging using the Delayed Enhancement technique can be useful to select patients with global or segmentary ventricular dysfunction, with high degree of fibrosis and at higher risk for clinical Ventricular Tachycardia. Objective: To improve the identification of predictors of Ventricular Tachycardia in patients with Chagas? Cardiomyopathy. Methods: This study assessed 41 patients with Chagas? Cardiomyopathy [30 (72%) males; mean age, 55.1 ± 11.9 years]. Twenty-six patients had history of Ventricular Tachycardia (VT group), and 15 had no Ventricular Tachycardia (non-VT group). All patients enrolled had Delayed Enhancement and segmentary ventricular dysfunction. In each case, the following variables were determined: left ventricular percentage of ventricular wall thickness impairment; percentage and Delayed Enhancement distribution in each segment. Results: No statistical difference regarding the Delayed Enhancement percentage between both groups was observed: VT group = 30.0 ± 16.2%; non-VT group = 21.7 ± 15.7%; p = 0.118. The presence of two or more contiguous transmural fibrosis segments was a predictor of Ventricular Thachycardia. Conclusion: The identification of two or more segments of transmural Delayed Enhancement by use of Cardiac Magnetic Resonance Imaging is associated with the occurrence of clinical Ventricular Tachycardia in patients with Chagas? Cardiomyopathy.